The impact of carbon insoles in cycling on performance in the Wingate Anaerobic Test - Koch, M.; Fröhlich, M.; Emrich, E.; Urhausen, A. (Journal of Science and Cycling, 2013)
The usage of innovative technologies in high performance cycling is essential. Special insole devices made of carbon are expected to have an impact on the anatomical and biomechanical structures of the foot. They aim to prevent cycling-specific overuse injuries, as well to increase output power. Therefore, the effects of a cycling-specific carbon insole were evaluated with respect to its impact on the output power in a Wingate Test (WAnT). 18 male cyclists and triathletes (age: 26.3 ± 5.6 years, height: 181.9 ± 4.7 cm, mass: 76.7 ± 4.4 kg, foot length 28.2 ± 0.8 cm) on at least a national level were tested for peak and mean power during three WAnT with randomized and blind application of a standard insole or the cycling-specific carbon insole. The mean power of the standard insole (790.6 ± 50.3 W) was in overall trials 0.6 % higher than with the carbon insole (786.0 ± 45.0 W). The peak power with the standard insole (891.7 ± 74.6 W) was 1.5 % higher than with the carbon insole (878.4 ± 64.9 W). Neither for mean power (P = 0.76) nor for peak power (P = 0.53) the difference was significant. The usage of the cycling-specific carbon insole thus shows similar output power values as standard devices.